ANALISIS HUBUNGAN CURAH HUJAN DENGAN KEJADIAN BANJIR DAN KEKERINGAN PADA WILAYAH DENGAN SISTIM USAHATANI BERBASIS PADI DI PROPINSI JAWA BARAT (ANALYSIS OF RELATIONSHIP BETWEEN RAINFALL AND FLOOD AS WELL AS DROUGHT EVENTS ON AREA WITH RICE ... - Woro Estiningtyas; Rizaldi Boer; Agus Buono (Agromet, 2009)
There are significantly decreasing of rainfall in wet season and dry season, and changed in onset of early season, that all of them can make crouded in plan of planting date, field actifity especially for food crops africulture. In the other side, climate is one of condition that has been ready and can not change, where probability of climate change will be reality that should be happened every time. Increasing frequency of climate extrem will give high impact in agriculture, especialy in rice-based farming system. This paper describes the climate risk based on statistical approaches. The climate risk is focused on flood and drought event. The analysis used was a chance occurrence based on time series data of rainfall and flood/droughts (affected and puso) based on median value from time series data. The goal of this research are : (1) to know rainfall critical value that can be influence flood and drought event in some of central food crops i West Java, (2) to know probability of flood and drought event in some of central food crops in West Java. The result of this research show that critical value of the rainfall that can be influence flood and drought event is very variety. Average of for flood event for paddy field near coastal based on median approach is 140 mm/month with probability 0,6. For another location, 166 mm/month with probability 0,68. Average of critical value of the rainfall for drought event is 64 mm/month for paddy field near coastal with probability 0,73. For another location, critical rainfall value is 119 mm/month with probability 0,76. For spesific research or detail scale (district or sub distric) we can use rainfall critical value and probablity based on data in that specific location because the data is more representative local riil condition.